A decision tree analysis applied to women aged 43–45: who should be referred for ovum donation?. Issue 1 (January 2022) - Bercovich, Or; Almog, Benny; Fouks, Yuval; Kalma, Yael; Hasson, Joesph; Azem, Foad; Cohen, Yoni
Abstract: Research question: In women at the advanced age of 43–45 years undergoing repeated IVF cycles with autologous oocytes, who has the highest chance for birth and who should be referred early to receive donor oocytes? Design: A retrospective cohort study was conducted at a university hospital reproductive centre. The computerized database of 394 women aged 43–45 years undergoing 1528 non-donor IVF or intracytoplasmic sperm injection cycles between 2010 and 2019 was analysed. A decision tree was developed, enabling a comprehensive study of a set of clinical parameters and the expected outcomes. Results: The cumulative clinical pregnancy rate was 15.0% (59/394) and the cumulative live birth rate was 8.4% (33/394). The decision tree developed to predict women who should be offered egg donation included age, poor ovarian response to stimulation, the number of top-quality embryos, dominant follicles, previous pregnancy or live birth, fertilized oocytes and body mass index. The model showed that a good ovarian response in the first cycle was the best predictor for live birth (13.3% gave birth). However, among women with poor responses, 7.1% of those who were younger than 43.5 years gave birth, and none of the women who were older than 43.5 years did. Conclusions: Women over 43.5 years old with fewer than four oocytes collected in their first IVF cycle should be offered ovum donation, since their live birth rate in subsequent cycles is negligible.